The past is prologue: towards a historico-narrative approach at the intersection of historical criminology and narrative criminology - Bleakley, Paul (Crime, media, culture, 2023)
There is great scope for narrative criminology and historical criminology to come together and, in collaboration, find ways for the practices of each to strengthen the other. Ultimately, both have a shared focus: the stories (past and present) that we use to make sense of crime, and the criminal justice system. This article argues for a historico-narrative approach to criminological research, wherein the research conducted by historical criminologists can be augmented by the types of subjective analysis that are central to narrative criminology. Similarly, the analysis of ‘stories’ that is the core business of narrative criminologists can only be advanced by a greater engagement with the concept of historical time.